Bioremediation of petroleum and petroleum products - Speight, James G.; Arjoon, Karuna K. (Salem, Mass. : Scrivener, 2012)
With petroleum-related spills, explosions, and health issues in the headlines almost every day, the issue of remediation of petroleum and petroleum products is taking on increasing importance, for the survival of our environment, our planet, and our future. This book is the first of its kind to explore this difficult issue from an engineering and scientific point of view and offer solutions and reasonable courses of action.
Includes bibliographical references and index.
Keywords: Bioremediation; Petroleum products -- Environmental aspects; Electronic books